2021
DOI: 10.3389/fmicb.2021.622068
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Salmonella enterica Leaf Internalization Varies Substantially According to the Method and Conditions Used to Assess Bacterial Localization

Abstract: In a previous study, comparing the internalization of S. enterica serovar Typhimurium in various leaves by confocal microscopy, we have demonstrated that the pathogen failed to internalize tomato leaves. Numerous reasons may account for these findings, yet one such factor might be the methodology employed to quantify leaf internalization. To this end, we have systematically studied leaf localization of a Green-fluorescent protein-labeled Salmonella strain in tomato, lettuce, and Arabidopsis leaves by surface s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The apoplast can be protective and provide bacteria with increased nutrient availability, however, this environment is exclusive to microbes that can successfully migrate there and tolerate the host immune response. Tomato leaves are relatively restrictive to S. enterica ingression (26,27), yet we found that S. enterica can access an apoplast that is watersoaked either by Xanthomonas infection or abiotically. Additionally, comparison of S. enterica populations between experiments sampled at 2.5 hours post-arrival and 3 days post-arrival indicates that S. enterica populations are stable within a healthy apoplast and increase within an infected one.…”
Section: S Enterica Successfully Colonized Uv-protected Niches Of Abi...mentioning
confidence: 74%
See 1 more Smart Citation
“…The apoplast can be protective and provide bacteria with increased nutrient availability, however, this environment is exclusive to microbes that can successfully migrate there and tolerate the host immune response. Tomato leaves are relatively restrictive to S. enterica ingression (26,27), yet we found that S. enterica can access an apoplast that is watersoaked either by Xanthomonas infection or abiotically. Additionally, comparison of S. enterica populations between experiments sampled at 2.5 hours post-arrival and 3 days post-arrival indicates that S. enterica populations are stable within a healthy apoplast and increase within an infected one.…”
Section: S Enterica Successfully Colonized Uv-protected Niches Of Abi...mentioning
confidence: 74%
“…The flagella- dependent localization of S. enterica to internal tissue in response to light has been demonstrated via confocal microscopy of lettuce leaf pieces submerged in S. enterica inoculum (25). However, tomato leaves have been shown to be impermeable to S. enterica internalization when compared with lettuce leaves under comparable conditions (26, 27). Whether or not phytopathogen infection could enhance the permeability of leaves to enteric pathogens was not addressed by these studies.…”
Section: Introductionmentioning
confidence: 99%
“…17,26 The plant tissue can therefore protect cells against decontamination procedures. In addition, because the cells can enter into leaves from wounds and open stomata, 20,21 the harvest cutting site may also be responsible for the bacterial internalization in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The cutting site may also be responsible for bacterial internalization in leaves, in addition to wounds and open stomata. 20,21 In industry, salads and baby-leaves can be cut using a mechanized harvester (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also shown that S. enterica colonization of plants is not limited to external plant surfaces. S. enterica can become internalized through roots and is able to actively bypass stomata to colonize the leaf apoplastic space ( Gu et al, 2011 ; Karmakar et al, 2018 ; Rodrigues Oblessuc et al, 2019 ; Chahar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%